2011
DOI: 10.1063/1.3576932
|View full text |Cite
|
Sign up to set email alerts
|

Responses of endothelial cells to extremely slow flows

Abstract: The process of blood vessel formation is accompanied by very minimal flow in the beginning, followed by increased flow rates once the vessel develops sufficiently. Many studies have been performed for endothelial cells at shear stress levels of 0.1-60 dyn/ cm 2 ; however, little is known about the effect of extremely slow flows ͑shear stress levels of 10 −4 -10 −2 dyn/ cm 2 ͒ that endothelial cells may experience during early blood vessel formation where flow-sensing by indirect mass transport sensing rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…Once astrocytes were infused and grown to confluence on 3D ECM gels, endothelial cells were introduced and allowed to attach to the astrocytes forming a continuous cell layer on the ECM with direct cell-cell contact. The co-cultured cells were exposed to a controlled low flow through the vascular channel (0.1 dyne/cm 2 )31, mimicking the capillary flow in the brain. Under this condition, the BMECs were grown to form intact barrier in the dynamic co-culture with astrocytes on the surface of 3D ECM after 48 h. These cells remained viable for one week after flow was introduced into the vascular microchannels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once astrocytes were infused and grown to confluence on 3D ECM gels, endothelial cells were introduced and allowed to attach to the astrocytes forming a continuous cell layer on the ECM with direct cell-cell contact. The co-cultured cells were exposed to a controlled low flow through the vascular channel (0.1 dyne/cm 2 )31, mimicking the capillary flow in the brain. Under this condition, the BMECs were grown to form intact barrier in the dynamic co-culture with astrocytes on the surface of 3D ECM after 48 h. These cells remained viable for one week after flow was introduced into the vascular microchannels.…”
Section: Resultsmentioning
confidence: 99%
“…Extremely low fluidic flow was applied to the medium channels to mimic the blood flow in the microvessels as described previously3146. The microdevice was perfused at a flow velocity at about 20 μL/min following cell seeding, and then the flow velocity in the medium channel was decreased to ~1 μL/min due to the split flow of the chip.…”
Section: Methodsmentioning
confidence: 99%
“…Such extremely low shear stress (<0.1 dyne/cm 2 ) can not only provide physiological microenvironment but also correlate with tissue morphogenesis and pathogenesis. 15,16 Although interstitial flow in bone has been reported elsewhere; 17 however, the mechano-responsive behaviors of MSCs in response to extremely low interstitial level of fluidic flow and the mechanism behind these phenomena are still elusive.…”
Section: Regulation Of Cell Migration and Osteogenic Differentiationmentioning
confidence: 98%
“…Past studies with flow have indicated that endothelial cells gradually orient and elongate along the direction of fluid flow under uniform shear stress, as evidenced by rapid inclination of cell junctions along the flow, and gradual reorganization of the cytoskeleton, especially with peripheral actin stress fiber formation [25-28]. Such reorientation may benefit the cells by altering the stress profile over the cell surface, by enhancing communication pathways for the conveyance of shearing-induced intracellular molecules, or potentially by improving cell-cell connections and flexibility in the context of a vascular monolayer [20,24,28-32].…”
Section: Introductionmentioning
confidence: 99%